Environmental Influence on the Aggressiveness in Children with Schizophrenia - Jūratė Sučylaitė; Jurgita Platakytė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija, 2019)
Background. This article analyzes aggressive behaviour of schizophrenic child and its characteristics. It examines what factors provoke aggressive behaviour, what activities are useful to strengthen their social adaptation. There are scientific articles with discussions about schizophrenic patients’ feelings, neurobiological activities, but it is a lack of concrete case analyses, helpful to understand psychological and social causes of schizophrenic patient aggressive behaviour, and to create methodical techniques how to work with these children having goal to reduce aggressive behaviour. The aim of this article is to explore psychosocial environmental impact on aggressiveness of children, suffering from schizophrenia. Methods. Qualitative research was selected, phenomenological observation and a short interview with children’s mothers and nurses were used for data collection, and the examination of the documents (drawings) was used, too. Data were summarized using qualitative content analysis, as well as grounded theory strategy. The study involved four school-age patients with schizophrenia. Recorded materials of observations and interviews were analyzed as the text. Results. Schizophrenic child has learned aggressive behaviour in the family; social rejection or sudden loss of warm emotional contact strengthened aggressiveness; aggressive actions occurred spontaneously and were directed to the imme diate surroundings; these actions were incomprehensible to people; emergence of noise provoked aggressive actions. Aggressive behaviour is associated with insecurity, low self-esteem, failure to understand the cause of aggressive behavior attacks reinforces alienation and hostility to the social world. Unconscious aggressiveness intensifes during its performance, so the behaviour is completely out of control; its consequences are related to the personality’s social devaluation. All these things are experienced as an access to the catastrophe from which the man cannot be saved, so the children focus on the crumbling world and inadequate attempts to escape, provoking conﬂicts. Quiet environment and drawing strengthens the self-esteem of individuals and calms. Conclusion. Personalized, targeted organization of leisure, responding to the interests of children with schizophrenia, creates the psychosocial environment, where the child’s safety increases, and aggressive behaviour trend reduces.